2006
DOI: 10.1002/iroh.200510839
|View full text |Cite
|
Sign up to set email alerts
|

Tufa Deposition in Karst Streams Can Enhance the Food Supply of the Grazing CaddisflyMelampophylax mucoreus (Limnephilidae)

Abstract: We studied the effect of carbonate depositions covering stone surfaces on the growth of larvae and the biomass of subsequent adults of the grazing limnephilid caddisfly Melampophylax mucoreus (HAGEN, 1861) in a laboratory rearing experiment. M. mucoreus is mainly distributed in karst streams characterized by calcium carbonate precipitations (tufa). We reared larvae of M. mucoreus on stones covered by calcareous tufa crusts as well as on stones from which these crusts were experimentally removed to assess the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In our study we did not observe any such inhibition. Phosphates may have been evacuated from the solution by colonizing microorganisms (Kock et al, 2006) which additionally produce extracellular polymers that become good places for nucleation of crystals. Moreover, colonized autotrophs utilize the CO 2 thus further promoting the calcite deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we did not observe any such inhibition. Phosphates may have been evacuated from the solution by colonizing microorganisms (Kock et al, 2006) which additionally produce extracellular polymers that become good places for nucleation of crystals. Moreover, colonized autotrophs utilize the CO 2 thus further promoting the calcite deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Casas & Gessner (1999) found that carbonate deposition on leaves slowed breakdown rates in a Mediterranean stream in Spain, apparently by reducing both physical fragmentation and biological decomposition. In an experiment in a German stream, Kock et al (2006) found that travertine deposits on stone surfaces increased algal biomass and led to higher larval growth rates and higher adult mass of Limnephilidae caddisflies. Carbonate deposits that formed on the exoskeleton of Gammarus (Amphipoda) reduced predation by salamander larvae in an experiment in another German stream (Ruff & Maier, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested that macroinvertebrate abundances are lower in travertine than in nontravertine reaches in both substrate cementing/layerforming (Minckley, 1963;Oberlin et al, 1999;Pitois et al, 2003;Alvarez & Pardo, 2007) and channel damming (Carter & Marks, 2007) types of travertine. Travertine deposition also may affect the abundance of algae (Pentecost, 1991;Kock et al, 2006) and leaf decomposition rate (Casas & Gessner, 1999;Carter & Marks, 2007), which potentially may affect macroinvertebrates indirectly through food resources. Whether travertine influences macroinvertebrate community structure, however, is among the issues that have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Tufa formation is also responsible for increasing the habitat surface for diverse organisms (Pentecost 2005). The rough surface of the tufa-covered substrate provides greater microhabitat complexity, and it supports increased algal growth compared to sediment without encrustations (Kock et al 2006). At sites of active tufa deposition this deposit is not only a substrate upon which periphyton develops: tufa is also embedded within the periphyton matrix, i.e.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%